Pattern formation in binary fluids confined between rough, chemically heterogeneous surfaces. - Verberg, R; Pooley, C; Yeomans, J; Balazs, A (2004)
Using a mesoscale model for hydrodynamics, we simulate driven flow of AB binary fluids past surfaces that contain well-defined roughness or asperities. The geometry and wetting properties of the asperities are found to have a dramatic effect on the flow patterns. We isolate conditions where the A fluid forms vertical bands that bridge the asperities and an imposed shear (or pressure gradient) drives the system to form monodisperse droplets of A within the B fluid. The size of the droplets can be tailored by varying the morphology of the asperities. The surfaces needed to create this rich dynamical behavior are used as the stamps in microcontact printing; thus, the parameter space can readily be accessed experimentally, and the predictions suggest an efficient method for forming emulsions with well-controlled morphologies.